Spiradiclis yuanyangensis (Rubiaceae), a new species from Yunnan, China - Wu, Lei; Liu, Cheng; Song, Xiao-Fei; Chen, You-Sheng (Phytotaxa, 2021)
Spiradiclis yuanyangensis is described and illustrated from Yunnan Province in southwestern China. It is morphologically most similar to S. petrophila H. S. Lo, but differs from the latter mainly by its stem pubescent, corolla tube 4–5 mm (vs. ca. 2 mm) long, and short-styled corolla inside without a villous ring. A detailed description, line drawings and colour photographs are provided, together with notes on conservation status.